Capture of Group A Streptococcus by open‐microfluidic CandyCollect device in pediatric patients - Wan‐chen Tu; Ingrid H. Robertson; Andrea Blom; Elena Alfaro; Victoria A. M. Shinkawa; Daniel B. Hatchett; Juan C. Sanchez; Anika M. McManamen; Xiaojing Su; Erwin Berthier; Sanitta Thongpang; Ellen R. Wald; et al. (Bioengineering & Translational Medicine)
Abstract State the Purpose Obtaining high‐quality samples to diagnose streptococcal pharyngitis in pediatric patients is challenging due to discomfort associated with traditional pharyngeal swabs. This may cause reluctance to go to the clinic, inaccurate diagnosis, or inappropriate treatment for children with sore throats. Here, we determined the efficacy of CandyCollect, a lollipop‐inspired open‐microfluidic pathogen collection device, to capture Group A Streptococcus (GAS) and compare user preference for CandyCollect, conventional pharyngeal swabs, or mouth swabs in children with pharyngitis and their caregivers. Results All child participants (30/30) were positive for GAS by qPCR on both the mouth swab and CandyCollect. Caregivers ranked CandyCollect as a good sampling method overall (27/30), and all caregivers (30/30) would recommend CandyCollect for children 5 years and older. Twenty‐three of 30 children “really like” the taste and 24/30 would prefer to use CandyCollect if a future test were needed. All caregivers (30/30) and most children (28/30) would be willing to use CandyCollect at home. Conclusion All participants tested positive for GAS on all three collection methods (pharyngeal swab, mouth swab, and CandyCollect). While both caregivers and children like CandyCollect, some caregivers would prefer a shorter collection time. Future work includes additional studies with larger cohorts presenting with pharyngitis of unknown etiology and shortening collection time while maintaining the attractive form of the device.